Chico Xavier, caridade e o mundo de César: um olhar sobre o modo de gestão da assistência social espírita em Uberaba-MG - Carisio, Camila Mendonça (2008)
Uberaba turned to be the center of public attention when the famous medium Chico Xavier arrived in the city, in 1959. Since then, the number of spiritist centers has quintupled and the practices of assistance have increased. Inside the doctrinaire universe of Spiritism, charity occupies a privileged place because it is essential for the spiritual evolution. Therefore, all spiritist centers do social assistance as a way of practicing charity. The main goal of this research was to identify and to understand the means of management of Spiritist Social Assistance in Uberaba-MG. Chanlat (1996) understands means of management as a set of administrative practices implemented by the organization to achieve their objectives. This research was guided by Grounded Theory principles (GLASER; STRAUSS, 1967), qualitative research method in which exists a close relationship between data gathering, data analysis and the substantive theory that develops as a consequence. Intensive interview was the main instrument of data gathering. Recording lectures as well. Spiritist organizations documents were also researched. The technique of analyzing and interpreting data used was the Content Analysis (BAUER, 2002) supported by the software Atlas/TI. They both led to the categories of analysis: Chico Xavier, Uberaba and the spontaneity , Without charity there is no salvation and Relationships with the world of Cesar . As a result of this analysis, we realized that, in the case of Uberaba, the traditionalism, linked to Chico Xavier, prevails and the spontaneity is a principle which is in the core of a constant confrontation between dichotomies freewill and determinism, spiritual and material, human and divine that constitute the spiritist universe in Uberaba. They trust in good spirits , or spiritual guides , or superior spirits , or spirituality whose are the orientation leaders to the tasks of assistance, in contradiction to the spontaneity quality because the human actions are the result of deliberate spiritual influence. Nevertheless, the spiritists managers in Uberaba assure and reassure the spontaneous feature of the spiritist social assistance management. There is also a clear resistance to assimilate the dictates of the World of Cesar human laws and rules because they believe that the divine commandments are sufficiently good.